Зүүн Азийн хамтын ажиллагааны явц, Монгол Улсын бодлогын тухайд (Journal of International Studies, 2013)
Зүүн Азийн хамтын ажиллагааны эхлэл, өнөөгийн явц. Зүүн Азийн хамтын ажиллагаанд оролцох Монгол Улсын хүсэл эрмэлзлэл. Түүнд тохиолдож буй бэрхшээл. Түүнийг гэтлэн давах тухай эрэгцүүлэл. Some Thoughts on the Participation in the East Asian Economic CooperationIn the last years the regional integration process has been developed intensively in the East Asia with the influences of such factors as, the rapid growth of global economy and its competition, regional economic and political security in the globalization era. Mongolia is located in this region, and trying to participate in these regionalization processes. It is not possible for us to join East Asian structures, including ASEAN, ASEAN+3, ASEAN+6 and EAS yet, because our country is not a dialogue partner of ASEAN. Therefore, the dialogue partnership with ASEAN is the first vision for our country. In order to achieve it we will actively participate in the market of ASEAN countries and expand the economic cooperation. The step to expand the economic cooperation is the fast industrialization in our country. Our main strategy will be: 1/Formulate the government strategy for joining to ASEAN and East Asian integration and plan the program of action for implementing it from present days step by step. The basic content of this program should be the work to industrialize urgently and precisely (correctly) 2/ Study the possibility to participate in several informal dialogue canals (Canal II) of East Asian Cooperation with the purpose for observing the integration processes of East Asia and introduce our country policies and share the ideas; 3/Try to participate in some projects and cooperation implemented by ASEAN countries, initiatively using our advantages which have been jointed the Treaty of Amity and Cooperation.